PELATIHANMANAJEMENORGANISASI PADA REMAJADUSUNKENAIBAN DAN PENCIL, DESAKENAIBAN, JUWIRING, KLATEN, JAWA TENGAH - Siti Hapsah Isfardiyana (UII, 2014)
Youth is the next generation that needs to prepare for future challenges. To facethe challenge of increasingly severe and the need to work in the society, the youth needto have the ability / soft skills such as leadership, speaking in front of people, working inteams and understand others. Organization plays an important role in the developmentof adolescent personality relation to the self-development into a container to haveleadership skills, public speaking, work in teams, understanding other people and managethings. Training on organizational management in adolescents Kenaiban and Pencil villageprovides motivation for adolescents to be more active in the organization Youth anddevelop themselves within the organization.